Evapotranspiration and Growth Responses of Kale (Brassica oleracea L. var sabellica) to Different Composition and Type of Planting Media - Saputra, Tri Wahyu; Ghuvara, Rihlana Ardhian; Bowo , Cahyoadi; Purnamasari, Ika; Wijayanto, Yagus; Ristiyana, Suci; Wirawan, Ahmad Agam (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Kale (Brassica oleracea L. var. sabellica) is a high-value horticultural crop in Indonesia that requires precise water management to enhance productivity. This study examines the effects of growing media composition and type on water use efficiency, evapotranspiration (ET), and growth performance using a Randomized Complete Block Design with ANOVA and Duncan’s Multiple Range Test (DMRT). Two factors were tested: (1) media composition (M1: soil: media mix = 1:1; M2: 3:1; M3: 1:3) and (2) media type (P1: rice husk biochar; P2: manure; P3: cocopeat). Results showed an average water consumption of 254.98 ± 131.3 ml/day and water use efficiency of 11.6 ± 4.3%. ETo, ETc fluctuated due to environmental factors. Using Blaney-Criddle, ETo averaged 6.18 mm/day with Kc of 1.8 ± 0.45, while Hargreaves yielded 12.24 mm/day with Kc of 0.9 ± 0.22. Cocopeat and a 3:1 soil-media mix yielded 162 g/plant and a potential yield of 1.8 tons per hectare. These findings highlight the importance of optimized growing media for increasing water spinach productivity in tropical greenhouse conditions and provide a quantitative integration of evapotranspiration analysis across various growing media compositions and types.